PEER GROUP SUPPORT DALAM MENINGKATKAN PENGETAHUAN ORANG TUA TENTANG TOILET TRAINING - Noki Rama DS; Yuni Sufyanti Arief; Ilya Krisnana (Pediomaternal Nursing Journal, 2014)
Toilet training is training or stages of child development to be able to control bowel movements or urination achievedthrough organ system maturity and learning involving critical elements such as muscles, nerves, and brain. Andenkopresis enuresis occurs because the child does not want to go through toilet training, and purpose of the researchwas to analyzed the influence of peer group support as a parents knowledge about toilet training in pre-school children.This research was a pre-experimental pre-post test design with purposive sampling a sample who did a pre-school childat the school play group Al-Anshor Medaeng Waru Sidoarjo. The population in this research was the total number ofparents with pre-school age children are in school at Al-Anshor Play Group Medaeng Waru Sidoarjo. Sampling withpurposive sampling technique and obtained a sample of 30 people. Analysis of the statistical test used was the Wilcoxonsigned rank test to answer the problems examined. The analysis uses statistical tests Wilcoxon signed rank test toanswer the problem under study. The results of research found the influence of peer group support to parents'knowledge level is p = 0.000, its probability is smaller than the value of α = 0.05. Terms this means that the peergroup support can upgrade the knowledge of parents about toilet training in pre-school children. Within support this peergroup, individuals find ways to do and function of a toilet training so that the level of parental knowledge about toilettraining be increased. Based on the analysis of data it ca